Phenotypic dissimilarity index: Correcting for intra‐ and interindividual variability when quantifying phenotypic variation. Issue 11 (17th August 2022) - Puglielli, Giacomo; Carmona, Carlos P.; Varone, Laura; Laanisto, Lauri; Ricotta, Carlo
Abstract: In trait‐based ecology, phenotypic variation (PVar) is often quantified with measures expressing average differences between populations standardized in the range 0–1. However, these measures disregard the within‐population trait variability. In addition, some of them cannot be partitioned between populations. These aspects can either alter their interpretation or limit their applicability. To overcome these problems, we propose a new measure, the phenotypic dissimilarity (PhD) index, to quantify PVar between populations in scenarios of varying within‐population interindividual trait variability. PhD can also quantify within‐population PVar while accounting for intraindividual trait variability. Using simulated and real data, we show that using the PhD index becomes important when the within‐population trait variability is not negligible, as in all ecological studies. By accounting for within‐population trait variability, the PhD index does not overestimate PVar across an environmental gradient compared to other estimators. Traits inherently vary within species. Accounting for such variability is essential to understanding species' phenotypic responses to environmental cues. The proposed PhD index will provide ecologists with a tool for quantifying PVar within species and compare it between species at different levels of biological organization. We provide an R function to calculate the PhD index.